EDUKASI CUCI TANGAN YANG BAIK BAGI ANAK ANAK DALAM UPAYA PENCEGAHAN COVID 19 - Hasbi, Andi Rizkiyah; Dewi, Sari Ratna; Fahmi, Ainul; Marni, Marni (Universitas Muhammadiyah Tapanuli Selatan, 2021)
This activity aims to provide education and how to wash hands for children to adopt a clean and healthy lifestyle (PHBS) in order to avoid the transmission of COVID-19. Hand washing educational activities are carried out by providing an explanation of the importance of washing hands with soap and rinsing with running water. The implementation of this service program is carried out so that the community can clearly understand what the purpose of washing hands properly is. Based on the results of the implementation of community service programs, it can be concluded that the educational activity